Acquisition of Basic Science Process Skills among Malaysian Upper Primary Students. (November 2015) - Ong, Eng Tek; Ramiah, Puspa; Ruthven, Kenneth; Salleh, Sabri Mohd; Yusuff, Nik Azmah Nik; Mokhsein, Siti Eshah
This study aims to determine whether there are significant differences in the acquisition of basic science process skills by gender, school location and by grade levels among upper primary school students. Using an established 36-item Basic Science Process Skills test that assesses the skills of observing, communicating, classifying, measuring, predicting and inferring with appropriate reliability and validity, the instrument was administered to 220 respondents - 80, 80 and 60 in Years 4, 5 and 6 respectively, drawn from two urban and two rural national primary schools in Perak. The data were analysed by gender and by location using an independent samples t-test, and by grade level using one-way ANOVA. The findings indicated that while there was no gender difference, significant differences in the basic science process skills were found between rural and urban students, favouring the latter, in terms of observing, communicating, classifying and inferring. The significant grade level differences were only observed between Year 4 and Year 6 students, favouring the latter, in terms of measuring, predicting and inferring. Possible reasons for the differences observed are discussed.